Clinical, electrophysiological, imaging, pathological and therapeutic observations among 18 patients with Rasmussen's encephalitis. (March 2016) - Pradeep, K.; Sinha, S.; Mahadevan, A.; Saini, J.; Arivazhagan, A.; Bharath, R.D.; Bindu, P.S.; Jamuna, R.; Rao, M.B.; Govekar, S.; Ravikumar, B.V.; Chandramouli, B.A.; et al.
Abstract: We studied the clinical, electrophysiological, imaging and pathological features of 18 patients with Rasmussen's encephalitis (RE). This descriptive study included 18 patients (six males, 12 females) with RE who were evaluated for demographic and phenotypic details, electroencephalogram (EEG) results, MRI results, pathological features, virological markers and outcome. Radiological staging as per Bien et al. and pathological staging in accordance with Robitaille et al. were performed. Simple partial seizures were the most common initial manifestation. During the disease course, epilepsia partialis continua (EPC) developed in 15/18 (83.3%) and hemiparesis in 17/18 (94.4%) patients. EEG revealed hemispheric slowing (100%), interictal epileptiform discharges (100%) and ictal pattern (44.4%). Brain MRI revealed unihemispheric focal cortical atrophy (100%), white matter changes (88.2%), basal ganglia-ipsilateral caudate and putamen involvement (50.0%) and progression of atrophy on serial MRI (100%). Unusual presentations in this series included late onset (n = 1), and isolated lingual EPC (n = 1). Diagnostic biopsies in two patients revealed Robitaille stage 3 disease. The six hemispherotomy specimens showed stage 2 disease in one, stage 3 in three and stage 4 in two cases. Heterogeneity in disease stage in the different neuroanatomical regions and within the same cortical segment reflected progression of immune-mediated damage. Immunomodulation provided only temporary benefit. Patients who underwent functional hemispherotomy had reduction in seizure frequency and improved quality of life. The clinical, EEG and MRI findings are in accordance with the established literature. MRI staging was concordant with Robitaille pathological staging. Immunomodulation did result in transient reduction in seizure frequency while surgery in six produced reasonable benefit.